Correction: Combining microfluidics and FT-IR spectroscopy: towards spatially resolved information on chemical processes. Issue 6 (10th October 2016) - Perro, Adeline; Lebourdon, Gwenaelle; Henry, Sarah; Lecomte, Sophie; Servant, Laurent; Marre, Samuel
Abstract : Correction for 'Combining microfluidics and FT-IR spectroscopy: towards spatially resolved information on chemical processes' by Adeline Perro et al., React. Chem. Eng., 2016, DOI: 10.1039/c6re00127k.